2012
DOI: 10.1097/inf.0b013e3182337ddb
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Leukopenia in YOUNG Febrile Infants

Abstract: We performed a 7-year registry-based retrospective study. We included 1365 infants younger than 3 months of age with fever without a source; 81 (5.9%) had <5000 leukocytes/mm(3). Among the 1021 well-appearing 29- to 90-day-old infants, prevalence of serious bacterial infection (SBI) was 13.8% for those with a normal white blood cell count, 6.8% for those with leukopenia (odds ratio, 0.45), and 36.6% for those with leukocytosis (odds ratio, 3.59). None of the 9 well-appearing febrile neonates with leukopenia de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, the value of these tests is controversial. Recent studies have shown that white blood cell (WBC) count has a poor value in the diagnosis of bacteraemia and other bacterial infections in these infants 7 8. In fact, WBC count has been relegated in the more recently developed scores to identify patients at higher risk for SBI9 10 and newer biomarkers as C reactive protein (CRP)10 and, mainly, procalcitonin (PCT)11 seem to be more useful to identify febrile young infants with bacterial infections 2 12…”
Section: Introductionmentioning
confidence: 99%
“…However, the value of these tests is controversial. Recent studies have shown that white blood cell (WBC) count has a poor value in the diagnosis of bacteraemia and other bacterial infections in these infants 7 8. In fact, WBC count has been relegated in the more recently developed scores to identify patients at higher risk for SBI9 10 and newer biomarkers as C reactive protein (CRP)10 and, mainly, procalcitonin (PCT)11 seem to be more useful to identify febrile young infants with bacterial infections 2 12…”
Section: Introductionmentioning
confidence: 99%
“…Gomez et al, 42 Gomez et al, 43 Mintegi et al, 44 sensitivity analyses did not differ significantly, lending confidence to findings of the primary analyses (Table 2).…”
Section: Resultsmentioning
confidence: 66%
“…Curiously, leukopenia in well-appearing infants was not found to be a risk factor for a poor outcome, thus contrasting with previous reports. 22,23 On the one hand, a significant number of GBS colonizations were isolated in locations other than the blood (20, 16.9%), mainly CSF (17, 14.4%). This reaffirms the current recommendation to perform a lumbar puncture, if it has not been done before, when GBS bacteremia is identified in infants under 3 months of age.…”
Section: Discussionmentioning
confidence: 99%